Education of Students in the Spirit of Military Patriotism is our Urgent Task - Ilkhom Botirov Saidullaevich (International Journal on Integrated Education, 2023)
This article is about strengthening the sense of military patriotism, self-control, responsibility, discipline, national pride among young people, which are the basis of the future in a modern rapidly developing society, play an important role in social and political life. The importance of educating such qualities as pride and honor, in strengthening the foundations of a great future state. Indeed, on the basis of the reforms carried out in the field of education in our country, educating students in a military-patriotic spirit is put forward as an urgent task.